Report to the Secretary of State for Transport and the Secretary of State for Levelling Up, Housing and Communities : Transport and Works Act 1992: Acquisition of Land Act 1981: Town and Country Planning Act 1990: Planning (Listed Buildings and Conservation Areas) Act 1990: Network Rail (Huddersfield to Westtown (Dewsbury) Improvements) Order 202[ ]: Application for Deemed Planning Permission: Applications for Listed Building Consent: Application for Certificates in Relation to Acquisition of Open Space.: Transport and Works Act 1992: Acquisition of Land Act 1981: Town and Country Planning Act 1990: Planning (Listed Buildings and Conservation Areas) Act 1990: Network Rail (Huddersfield to Westtown (Dewsbury) Improvements) Order 202[ ]: Application for Deemed Planning Permission: Applications for Listed Building Consent: Application for Certificates in Relation to Acquisition of Open Space. (2022) - Unknown
No abstract available